Asuhan Keperawatan pada Ny.D dengan Gangguan Sistem Endokrin: Diabetes Melitus di Ruang Kemuning RSUD dr. Soeselo Kabupaten Tegal - Lulu Rahmawati; Esti Nurjanah; Wawan Hediyanto (STIKES Columbia Asia Medan, 2024)
Diabetes mellitus, also called diabetes, is a serious disease caused by the inability of the pancreas to produce insulin effectively, leading to an increase in blood glucose. In recent years, the number of diabetes cases has increased (Masturoh & Anggita, 2018). According to WHO data, Indonesia occupies 7th position in the world with 10 million people suffering from diabetes and it is estimated that there will be 21.3 million people in 2021. Because it is the only country in Southeast Asia with the highest number of diabetes mellitus sufferers, Indonesia contributing to the increasing prevalence of diabetes in Southeast Asia (Anisah et al., 2023). The purpose of this writing is to find out and provide nursing care to Mrs. D with endocrine system disorders: diabetes mellitus in the kemuning ward of RSUD dr. Soeselo Tegal Regency in accordance with nursing standards. The method used is descriptive and data collection methods. From case observation, it was found that the main complaint was weakness. There were three diagnoses found, namely instability of blood glucose levels, acute pain and knowledge deficit. Interventions are structured based on the theory of SDKI, SLKI and SIKI as well as on the client's condition and can be implemented.